Factors Influencing Running Velocity at Lactate Threshold in Male and Female Runners at Different Levels of Performance - Støa, Eva Maria; Helgerud, Jan; Rønnestad, Bent R.; Hansen, Joar; Ellefsen, Stian; Støren, Øyvind (Frontiers in Physiology, 2020)
Background: The primary aim was to examine the relationship between lactate threshold (LT%) expressed as percentage of maximal oxygen uptake (VO2max) and running velocity at LT (LTV). A secondary aim was to investigate to what extent VO2max, oxygen cost of running (CR), and maximal aerobic speed (MAS) determined LTV. A third aim was to investigate potential differences in LT% and LTV between elite, national and recreational runners, as well as possible gender differences regarding VO2max, CR, LT% and LTV. Methods: 75 competitive runners (37 males and 38 females) with an average VO2max of 63.0 ± 9.3 mLkg-1min-1, and an average LTV of 13.6 ± 2.3 kmh-1 were tested for VO2max, LT%, LTV, MAS, and CR. Results: LT% did not correlate with LTV. With an r - value of 0.95 (p0.001) and a standard error of estimate of 4.0%, the product of MAS and individual LT% determined 90% of LTV, outside a range of ± 0.27 kmh-1. LTV increased with higher performance level. However, LT% did not differ between elite, national and recreational runners. Female runners had 2.5% higher LT%, 8% lower LTV and 21% lower VO2max, but 9% better CR than male runners. Conclusion: LT% did not correlate with LTV. The product of MAS and LT% correlated strongly with LTV. There were no differences between elite, national and recreational runners regarding LT%, but female runners had higher LT% than the male runners. Female runners at the same relative performance level had lower LTV and VO2max, but better CR than male runners.